Cinzas do Norte, de Milton Hatoum, um romance de formação - PINHEIRO, Lucilia Lúbia de Sousa (Universidade Federal do Pará, 2019)
The present study shows the novel Cinzas do Norte (2005), from the writer Milton Hatoum, according to the Bildungsroman concept.Firstly, this work is foccussed on what R.Selbmann (1994) considers the ―obrigatory instance‖ of a Bildungsroman such as the presence of the formation(scholar or professional). To include the reader into this discussion the studies produced in Brazil and into the Amazon context are approached, taking novels characterized as Bildungsroman in therms of formation or education. In the second place the study is about the structural form of the novel related to narrator,plot, time and space. Brings the possibility of lecture of the Hatoum‘s novel starting with the point of formation. This study brings also the reception of the novel, emphasizing the memorialistic aspect point by the critic.